The Dimension of Sustainability in Engineering Education in Cuba - José Antonio Díaz Duque (Foro de Educación, 2015)
The human species crosses one of the most complex and dangerous stages in its development. The disordered growth of the production of goods and services, the irrational and unequal consumption, as well as the inequitable distribution, without keeping in mind the limits that impose the natural resources, has placed it in the vortex of an existence crisis. Numerous they have been the contributions of the scientific and technological knowledge, but at the same time they have provoked negative enormous impacts in the natural systems. The engineering have contributed to the human development, but not in a sustainable way. The main objectives of the present work consist in to identify the sustainability demands for the engineering and to specify the key aspects in the formation of the engineers to contribute to the sustainable development of the society. In consequence, it is proposed the Decalogue of the sustainability for the engineering and it is presented an outline for the implementation of the sustainability dimension in engineering education. Finally the Cuban situation is analyzed in this respect and it is proposed the step to a new cycle of improvement of the plans and study programs, with the transformation of the professional’s model based on the sustainability problems. How to reference this article Díaz Duque, J. A. (2015). La Dimensión de la Sostenibilidad en la Enseñanza de las Ingenierías en Cuba. Foro de Educación, 13(19), 241-262. doi: http://dx.doi.org/10.14516/fde.2015.013.019.011